36 Phenotypic predictors of genotype positivity in probands with hypertrophic cardiomyopathy (HCM). (6th October 2022) - Ranganathan, D; Killian, M; Moore, D; Gallagher, M; Gorrian, CMc; Galvin, J
Abstract : Introduction: HCM is the most common inherited cardiomyopathy and a leading cause of sudden cardiac death (SCD). With growing access to genetic testing, and incorporation of genetics in diagnosis and personalised management, it is critical to better understand the phenotypic predictors of pathogenic or likely pathogenic (P/LP) variants. This has implications for family screening, as well as resource planning. Aims: To the yield of genetic testing in unexplained left ventricular hypertrophy (LVH) and to further identify the phenotypic predictors of genotype positivity in HCM patients. Method: A retrospective single centre study of 213 patients, who had undergone comprehensive HCM testing was carried out. Thirteen patients were excluded (6 - SCD, 7 - significant, non-HCM gene). Demographic information was obtained from clinic data and each patient's LVH pattern was then classified as sigmoid, concentric, reverse or apical based on trans-thoracic echocardiogram (TTE). Pathogenicity of variants was classified according to the American College of Medical Genetics (ACMG) criteria. Results: A total of 200 patients were included in the analysis, of which 167 had TTE undertaken in the study centre, allowing for further detailed phenotype analysis. In the 200 patients, the mean age was 53.85 (SD 14.04) with 151 (75.5%) being male, 66 patients (17.5%) had an underlying diagnosis of hypertension (HTN) with an average of 1 anti-hypertensive agent (58.7%), 30 patients had a family history of SCD (17.5%), 41 patients (24.6%) had underlying atrial fibrillation, 53 patients had a history of ventricular arrhythmia (26.5%), 61 patients had an implantable defibrillator (31.8%), 3 patients had an aborted cardiac arrest (1.5%), 7(3.5%) patients had septal myomectomy and 4(1%) patients required a cardiac transplant. Echocardiographic analysis showed a mean interventricular septal thickness in diastole (IVSd) of 19.8mm (SD 4.3) and the left ventricular internal diameter in diastole (LVIDd) was 44.2mm (SD 8.3). Genetic testing was appropriate in 195 patients (97.5%), with the remainder 4 patients had IVSd <15mm and 1 patient had moderate aortic stenosis. A core HCM panel (17 genes) was performed in 192 patients, 6 patients had extended HCM (69 genes) and 2 patients had global CM panel (109 genes), with a yield, of LP/P in 58 (30.2%), 3 (50%) and 1 (50%) within each respective panel. No gene, including likely benign (LB) and benign (B), was identified in 98 patients (49%). MYBPC3 and MYH7 were the most frequently identified variants ( figure 1 ). Sub-analysis of 167 patients with TTE showed the concentric pattern of LVH was most frequent at 31.7% (53 patients) followed by reverse, apical and sigmoid patterns ( table 1 ). Younger patients, females, family history of SCD, normotensive with reverse pattern LVH (p value <0.001) predicted LP/P variant identification ( table 2 ). Conclusion: Genetic testing was appropriately offered and comparable to international guidelines (33.3% ESC, 32% AHA). In patients with unexplained LVH being younger, female, having a family history of SCD, normotensive and a reverse pattern LVH on TTE predicted a higher yield of LP/P variant identification. This study has implications for supporting better phenotype-based genetic counselling and resource usage for HCM patients.